Thermodynamics and Kinetics of the Reaction of Catalytic Dismutation of Chlorosilanes in the Vapor Phase in the Temperature Range of 353–393 K - Georgy Mochalov; Yegor Stolmakov; Olesya Zhuchok (ChemEngineering, 2023)
Currently, the most common method of silane synthesis for electronics and photovoltaics is trichlorosilane (TS) dismutation. TS dismutation proceeds in the form of a reactions cascade, therefore its study is of both practical and scientific interest. The results of calculating the equilibrium composition of the reaction mixture in the vapor phase based on literature data from various sources were not reliable. Therefore, the dependence of the composition of the reaction mixture on the time of contact of the TS vapor with the catalyst under static conditions was experimentally investigated. The stationary composition of the mixture, close to equilibrium, was determined. A good agreement of the obtained results with the literature data in one of the sources was shown. The kinetics of the dismutation reaction of TS and dichlorosilane (DCS) was carried out by the flow method. As a result of regression analysis of experimental data, the rate constants of the direct and reverse dismutation reactions of TS, DCS, and monochlorosilane (MSC) were obtained. The rate constants were used to calculate the equilibrium composition of the reaction mixture. A good agreement between the calculated and experimental data was shown.